The Role of the Stock Market in the Development of Social Infrastructure - Fayziev Z.A. (Genius Journals, 2023)
Possibilities are being considered to expand the use of stock market instruments to finance social infrastructure, and, in particular, debt financing through municipal bonds. The main directions for the formation and development of the market for domestic municipal bonds in Uzbekistan are proposed
Keywords: Securities market; social infrastructure; investments